Polypore fungus beetles (Coleoptera: Tetratomidae) in a remnant of semi-deciduous forest of the Brazilian Cerrado: checklist and the description of a new species of Eustrophopsis Champion, 1889 - Begha, Bruno Piotrovski; Souza, Isabella Magalhães De; Oliveira, Sarah Siqueira (Zootaxa, 2024)
Tetratomidae Billberg, 1820 is a small family of tenebrionoid beetles that primarily feed on polypore fungi. Their Neotropical diversity remains poorly known, with most recent studies concentrating on Nearctic and Palearctic species. The few records from the neotropics are from samplings in the Atlantic Forest or Amazon Rainforest. Here we present illustrations of genitalia and photos of two species of Eustrophopsis Champion, 1889, E. laurae sp. nov. and E. bilunulata Pic, 1912. The samplings were carried out with malaise traps in the Parque Estadual Altamiro de Moura Pacheco (PEAMP), Goiás, Brazil, a remnant Cerrado mostly covered by semi-deciduous forest. These species represent the first records of Tetratomidae for the Brazilian Cerrado since their original descriptions, elucidating the paucity of studies on the fauna of Coleoptera in Brazil. This research is part of our ongoing efforts to better understand the insect diversity of this region, especially in current scenarios of rapid deforestation and biodiversity loss.